Development and validation of knowledge, attitude and practice questionnaire on the consumption of gum Arabic among users in Malaysia - Abdul Halim, Aimi Syifaa'; Mohd. Abdul Majid, Hayati Adilin; Mat Issa, Zuraini; Hussin, Ruhaya; Yusoff, Sarah (Asian Scholars Network, 2020)
Globally, the Gum Arabic (GA) market has been expected to grow, particularly due to its multi-functionality and health benefits. Various clinical studies and functional properties studies of GA have been conducted. But the study from users' insight is scarce, resulting in the inadequacy of validated questionnaire of knowledge, attitude and practice of users' GA consumption. Hence, this study aimed to validate the questionnaire focusing on knowledge, attitude and practice of GA consumption among Malaysian users. A total of 100 respondents completed an online self-administered questionnaire. Construct validity was assessed using exploratory factor analysis with principal factoring axis and oblique rotation. Based on the factor analysis output, only factor loading of 0.5 and higher were considered. The number of factors retained was then assessed through the scree plot and parallel analysis. Finally, out of 43 items, 20 items remained as validated and reliable questions. The original Knowledge construct is represented separately as "objective knowledge" (OK) and "subjective knowledge" (SK). Attitude and practice remained as one factor each. All constructs have high reliability of Cronbach's Alpha ranging from 0.875 to 0.959. The result obtained has indicated that the instrument developed has high validity and reliability. The findings are essential and useful assessment tool to evaluate knowledge, attitude and practice of GA consumption among users in Malaysia.